2016
DOI: 10.1071/ch16443
|View full text |Cite
|
Sign up to set email alerts
|

Binder-Free TiO2 Monolith-Packed Pipette Tips for the Enrichment of Phosphorylated Peptides

Abstract: A macroporous TiO 2 monolith-entrapped pipette-tip was developed through a binder-free packing method for convenient phosphorylated peptide enrichment. A detection limit of 1 ng mL À1 for phosphorylated peptide is achieved, showing a better enrichment efficiency compared with the commercial pure TiO 2 -embedded NuTip.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The phosphopeptide signals were less interfered with by those of the nonphosphopeptides and showed that the enrichment performance of the resultant TiO 2 -CM material was higher than that of the commercial TiO 2 material. Compared with similar materials used in MOAC and IMAC, the TiO 2 -CM material exhibited good selectivity on phosphopeptides. This indicated that the resultant TiO 2 -CM material possessed excellent selectivity for phosphopeptide enrichment and a stronger anti-interfering ability for nonphosphopeptides than the commercial TiO 2 material.…”
Section: Results and Discussionmentioning
confidence: 98%
“…The phosphopeptide signals were less interfered with by those of the nonphosphopeptides and showed that the enrichment performance of the resultant TiO 2 -CM material was higher than that of the commercial TiO 2 material. Compared with similar materials used in MOAC and IMAC, the TiO 2 -CM material exhibited good selectivity on phosphopeptides. This indicated that the resultant TiO 2 -CM material possessed excellent selectivity for phosphopeptide enrichment and a stronger anti-interfering ability for nonphosphopeptides than the commercial TiO 2 material.…”
Section: Results and Discussionmentioning
confidence: 98%
“…Sun, and A. Nouwens on 'Binder-free TiO 2 Monolith Packed Pipette-Tips for the Enrichment of Phosphorylated Peptides'. [9] Denis Evans (ANU) is the 2015 winner of the David Craig Medal of the Academy of Science and has presented a research paper with co-workers Stephen Williams and Debra Bernhardt on 'A Derivation of the Gibbs Equation and the Determination of Change in Gibbs Entropy from Calorimetry'. [10] Jeffrey Reimers (UTS and Shanghai University) is the 2016 winner of the David Craig Medal of the Academy of Science and has presented an account entitled 'Putting David Craig's Legacy to Work in Nanotechnology and Biotechnology'.…”
mentioning
confidence: 99%